Associations of adiposity measurements with thyroid nodules in Chinese children living in iodine-sufficient areas: an observational study. Issue 10 (30th October 2017) - Wang, Na; Fang, Hong; Fu, Chaowei; Huang, Peixin; Su, Meifang; Jiang, Feng; Zhao, Qi; Chen, Yue; Jiang, Qingwu
Abstract : Objectives: Obesity has been found to be associated with an elevated risk of thyroid nodule(s), mainly in adults; however, evidence for this association in children was limited. The objective of this study was to investigate the association of adiposity and thyroid nodule(s) in children living in iodine-sufficiency areas. Setting and participants: We conducted a cross-sectional study of 1403 Chinese children living in the East Coast of China in 2014. Outcome measures: Anthropometric measures including height, weight and waist and hip circumferences were taken, and body mass index (BMI), body surface area (BSA) and waist–hip ratio (WHR) were then calculated. Thyroid ultrasonography was performed to assess thyroid volume and nodules. Results: Based on BMI, 255 (18.17%) children were overweight and 174 (12.40%) were obese. Thyroid nodule(s) was detected in 18.46% of all participants and showed little age and sex variations. As compared with normal-weight children, obese children experienced significantly higher risks for solitary (OR 2.07 (95% CI 1.16 to 3.71)) and multiple (OR 1.67 (95% CI 1.03 to 2.70)) thyroid nodules. Similar associations with thyroid nodule(s) were observed with adiposity measured by waist circumference and BSA, but not WHR. There were no notable differences in the associations between children consuming iodised and non-iodised salt. Conclusions: These findings provide further evidence that childhood obesity is associated with the risk for thyroid nodule(s).